2005
DOI: 10.1136/gut.2004.062174
|View full text |Cite
|
Sign up to set email alerts
|

Cholera toxin subunit B inhibits IL-12 and IFN-  production and signaling in experimental colitis and Crohn's disease

Abstract: Background and aims: Cholera toxin B subunit (CT-B) is a powerful modulator of immune responses. The authors have previously demonstrated that oral administration of recombinant CT-B (rCT-B) is able to prevent and cure the Crohn's disease (CD)-like trinitrobenzene sulfonic acid (TNBS) mediated colitis. In this study they extended their observations and examined if rCT-B interferes with the molecular signaling underlying the Th1 type response both in TNBS colitis and in ex vivo human CD explants. Methods: TNBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 43 publications
3
41
3
Order By: Relevance
“…The powerful adjuvant, immunomodulatory and oral tolerance inducing properties of CT and its B subunit have been shown to prevent experimentally induced autoimmune diseases and allergies in various preclinical rodent models (17,(32)(33)(34). CT has been reported to modulate the expression of both Th1 and Th2 cytokines (16,17,19,20,22). Although the results of different studies vary, most researchers agree that CT downregulates the proinflammatory cytokines IL-12, IL-6 and TNF-α, and upregulates the anti-inflammatory cytokines IL-10 and Tgf-β (16,17,19,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful adjuvant, immunomodulatory and oral tolerance inducing properties of CT and its B subunit have been shown to prevent experimentally induced autoimmune diseases and allergies in various preclinical rodent models (17,(32)(33)(34). CT has been reported to modulate the expression of both Th1 and Th2 cytokines (16,17,19,20,22). Although the results of different studies vary, most researchers agree that CT downregulates the proinflammatory cytokines IL-12, IL-6 and TNF-α, and upregulates the anti-inflammatory cytokines IL-10 and Tgf-β (16,17,19,22).…”
Section: Discussionmentioning
confidence: 99%
“…For that, CT is considered an attractive component of oral tolerance-based immunotherapy schemes for the treatment of immune-related disorders (15)(16)(17). CT activates antigen-presenting cells (16,(18)(19)(20)(21), induces Tregs and expands their population (16,17,19), affects the expression of cytokines and modulates both Th1 and Th2 immune responses (16,17,20,22). Interestingly, these immune events have been shown to affect carcinogenic processes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, studies are currently underway to elucidate the mechanism and the potential contribution of CTBp-induced colonic immune cell profile in the context of mucosal healing. While CTB's mucosal healing potential has not been previously reported, past studies have shown that the protein can blunt intestinal inflammation of Crohn's disease in a mouse model and in a small-scale clinical trial (73,74). In the mouse model, CTB inhibited the production of IFNγ and IL-12 in colon lamina propria mononuclear cells, which was reproduced in human Crohn's disease explant tissues (73).…”
Section: Summary Of the Present Ctbp Studiesmentioning
confidence: 99%
“…While CTB's mucosal healing potential has not been previously reported, past studies have shown that the protein can blunt intestinal inflammation of Crohn's disease in a mouse model and in a small-scale clinical trial (73,74). In the mouse model, CTB inhibited the production of IFNγ and IL-12 in colon lamina propria mononuclear cells, which was reproduced in human Crohn's disease explant tissues (73). In the present study, hallmarks of anti-inflammatory effects (decreased body weight loss, inflammation scores and inflammatory cytokine mRNA/protein levels) were noted in the DSS colitis model after CTBp administration (Chapter 3); similar to the findings from the Crohn's disease experiments.…”
Section: Summary Of the Present Ctbp Studiesmentioning
confidence: 99%
See 1 more Smart Citation